Effort of Islamic Religious Education Teachers to Form Spiritual Attitude of Student - Misgiyanti, Nova; Romelah, Romelah; Mardiana, Dina (Journal of Modern Islamic Studies and Civilization, 2025)
The objectives of this study are: (1) To examine in depth the spiritual attitude of grade XII students at Tugumulyo State High School. (2) To study the efforts of Islamic religious education teachers in shaping the spiritual attitude of grade XII students at Tugumulyo State High School. This research is qualitative with a descriptive analysis approach, so the researcher will go directly to the field (field research) to dig up as much information as possible needed in this research. The data collection techniques used by the researcher are observation, interviews, and documentation. The results of this study conclude that (1) the spiritual attitude of grade XII students at Tugumulyo State High School, including the following: Getting used to and carrying out prayers in congregation and on time, getting used to reciting the Qur'an or reciting, always saying thayyibah sentences, getting used to praying before and after doing activities, and politeness in attitude. (2) The efforts of Islamic Religious Education Teachers in shaping the spiritual attitude of grade XII students at Tugumulyo State High School, including the following: Teachers use methods to form spiritual attitudes, carry out and habit of behaving following the demands of karimah exemplified by the Prophet, get used to dhuha prayers and congregational dzuhur prayers to improve worship discipline, hold study or recitation activities for additional knowledge about Islamic teachings,  development of religious behaviour through Islamic religious education lessons, and providing punishment according to students' violations.